Visualization of pulmonary vein reconnections using dynamic mapping in redo procedures for patients with atrial fibrillation. (19th May 2022) - Parreira, L; Rossillo, A; Del Greco, M; Mantovan, R; Fantinel, M; Bottoni, N; Bianco, E; Bacchiega, E; Tao, C; Rossi, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Pulmonary vein (PV) reconnection is commonly associated with recurrence of atrial fibrillation (AF) after the initial catheter ablation procedure. Visualization and identification of PV reconnections are critical during repeat procedures. Purpose: To examine the use of dynamic mapping (LiveView) in combination with a high-density mapping catheter (HD Grid) in the recognition of PV reconnections in redo AF ablation procedures. Methods: Acute procedure data from 81 patients were prospectively collected. Mapping catheter selection and the use of LiveView was determined at the physician's discretion. For cases where LiveView was used, the location and number of gaps from the previous procedure were identified using both standard mapping and dynamic mapping separately. Results: Most of the patients included in the analysis were treated for paroxysmal AF (PAF: n=63/81, 77.8%). Dynamic mapping data was incorporated in 50 PAF cases and 15 persistent AF cases. Within these 65 cases, standard mapping identified a total of 120 PV gaps whereas LiveView identified a total of 138 PV gaps; gaps were most frequently identified on the right PVs, especially in the anterior region (Table1). A contact force-sensing ablation catheter was commonly (n=64/81, 79%) used by the operators. The right anterior region was ablated with an average contact force of 13.8±3.1g and Lesion index (LSI) of 5.2±0.7 at a power of 35.8±8.4W. Non-PV ablation was performed in 38 (46.9%) patients; the most common lesion sets were roofline, cavotricuspid isthmus (CTI) line, and mitral isthmus line. Acute PV isolation was achieved in all patients at the end of the procedure. Conclusion: Data from this analysis suggest the incorporation of dynamic mapping data may help reveal more PV reconnections compared to standard mapping. Additional study is needed to assess the long-term clinical outcomes when regional dynamic mapping data is used to identify PV reconnections in repeat procedures.